Four weeks of exercise regimen for sedentary workers with rounded shoulder posture: a randomized controlled study - Gunaydin, Ozge Ece; Ertekin, Ersen; Gunaydin, Gurkan (São Paulo Medical Journal, 2023)
BACKGROUND: Rounded shoulder (RS) posture causes neck and shoulder pathologies. Mechanical correction taping (MCT) is often incorporated into postural corrective therapies; however, its effects on muscle stiffness are unclear. OBJECTIVE: We investigated the effect of MCT with different tape fabrics, along with exercise, on upper trapezius and pectoralis minor muscle stiffness and the posture of sedentary workers. DESIGN AND SETTING: A randomized controlled study was performed at Aydın Adnan Menderes University, Aydın, Turkey. METHODS: The study included 39 workers with RS posture. Two intervention groups (performance tape: PT and classic tape: CT) were taped twice a week and administered a home exercise program for 4 weeks. The control (C) group performed only home exercises. RS was measured using an acromion-testing table (AT), stiffness using shear wave elastography ultrasound, and shoulder angle (SA) using a smartphone application at baseline and 4 weeks. Time and group interactions were determined using 3 × 2 mixed analysis of variance. RESULTS: Intragroup analyses revealed a significant main effect of time on AT distance (η2 = 0.445) and SA (η2 = 0.325) in the PT and C groups (P < 0.05) and left upper trapezius stiffness (η2 = 0.287) in the CT and C groups (P < 0.05). In the post hoc analyses, no difference was noted between the groups from baseline to 4 weeks (P > 0.05). CONCLUSION: Scapular MCT added to postural exercises did not show any difference between the intervention groups and controls in terms of muscle stiffness and posture in sedentary workers.